Persepsi dan Pengalaman Siswa SMPIT Sahabat Alam terhadap Green Education dan Program Eco-School - Saputra, Teguh Aji; Ruhama, Alma Siti; Nurandini, Nurandini; Ramadhan, Muhammad Iqbal; Regina, Putri Rasta (Muttaqien Publsihing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
This study aims to understand the perceptions and experiences of students of SMPIT Sahabat Alam regarding Green Education and the Eco-School program. The background emphasizes the importance of environmental education in addressing global issues, encouraging educational institutions to shape an environmentally conscious generation. This study explores how students perceive ecological education in their schools. The method used is a qualitative approach with a case study design, through in-depth interviews with fifteen students and participant observation of Eco-School activities. The results show that students have a favorable view of Green Education and Eco-School, considering them relevant and providing meaningful learning experiences. Students reported increased awareness, motivation, and positive behavior towards the environment. This paper provides a comprehensive overview of the effectiveness of environmental education programs in secondary schools and factors that influence student participation. Recommendations include developing more interactive programs and collaboration between schools and communities to strengthen the impact of environmental education on shaping students' sustainable attitudes.